Saving Afghanistan - Krishnappa, V.; D'Souza, Shanthie Mariet; Singh, Priyanka; Institute for Defence Studies and Analyses (New Delhi Academic Foundation in association with Institute for Defence Studies and Analyses, 2009)
Contributed articles presented at the conference at the Institute for Defence Studies and Analyses in February 2008.
Includes bibliographical references.
Keywords: Conflict management -- Afghanistan -- Congresses; Afghanistan -- Politics and government -- 2001- -- Congresses